Temporary works part two : further principles of design and construction - Filip, Ray (Emerald Publishing Limited, 2025)
Temporary Works Part Two: Further Principles of Design and Construction provides authoritative and comprehensive guidance on key areas of temporary works for practising engineers. Building on the successful format of Temporary Works: Principles of Design and Construction, the book provides 18 entirely new chapters covering recent developments in this field. With contributions from over 20 industry experts, topics include construction safety; modern methods of construction; structural steelwork; structural and geotechnical investigations for temporary works; digital temporary works and AI, sustainability, and low carbon. The book presents key learning from major projects, and also provides guidance on the use of temporary works across a number of sectors including nuclear; rail, tunnelling, the marine environment and building refurbishment. Temporary Works Part Two is an essential reference for temporary and permanent works designers, engineers, technicians, temporary works coordinators and supervisors, and also contractors looking to minimise costs, maximise efficiency and ensure the safety of those working on site.
Includes index.
Keywords: Engineering.; Technology & Engineering -- Construction -- General.; Construction and heavy industry.; Building construction and materials.; Building skills and trades.; elektronické knihy; electronic books